Need analysis of interactive karaoke multimedia to improve early childhood's verbal communication ability - Miyarso, Estu; Nugroho, Ariyawan Agung; Wulandari, Rina (JOURNAL OF EDUCATION, 2015)
This study was aimed at determining 1) the relationship between the familyculture and the children interactive karaoke multimedia product development needs, and 2) the needs level of the multimedia interactive karaoke for early childhood to improve their language skills. This study was a survey involving early childhood teachers and parents in Bantul Regency, Kulon Progo Regency, and Yogyakarta City using purposive sampling to obtain the respondents. Data were collected by means of questionnaires, observation sheets, and interview sheets. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed that 88% of early childhood teachers and 79% of early chilhood parents agreed to the need of the development of multimedia computers to improve early childhood's language skills. Children's language abilities are inï¬‚ uenced by their habits in listening, speaking, singing, and also drawing. The facilities and infrastructure availability also affect the children's language abilities. Family culture is not only a structure, but also an interaction and communication pattern between a family component, especially the children-parent relationship. The most inï¬‚ uencing factor that affects a family culure is the family socio-economic factors. A good-enough economic families are likely to have a good literate culture which will affect the children's language ability, because it is supported by a good access to the facilities